Mericarp micromorphology and anatomy of Salvia hedgeana Donmez, S. huberi Hedge and S. rosifolia Sm. (section Salvia Hedge, Lamiaceae) - Buyukkartal, Hatice N.; Kahraman, Ahmet; Colgecen, Hatice; Dogan, Musa; Karabacak, Ersin (Acta Botanica Croatica, 2011)
Mericarp (nutlet) micromorphology and pericarp structure of three morphologically similar endemic Salvia species; Salvia hedgeana, S. huberi and S. rosifolia were investigated using LM, SEM and TEM. Salvia hedgeana has larger mericarps and abscission scars than S. huberi and S. rosifolia. Mericarp length to width ratio ranges from 1.11 in S. hedgeana to 1.60 in S. huberi. Mericarp shape is mainly ovoid, rarely broadly ovoid in S. hedgeana, and oblong in S. huberi. The mericarp surface sculpturing pattern in all species is colliculate. However, exocarp cells are pentangular-hexangular in S. hedgeana, irregular in S. huberi and rounded and smaller in S. rosifolia. In Salvia huberi anticlinal walls are undulate whereas in S. hedgeana and S. rosifolia anticlinal walls are straight. Salvia hedgeana was distinguished from the others by the thickest pericarp (146–185 μm). The sclerenchymatous region significantly varied between the species. It was 84–99 μm in S. hedgeana, 56–82 μm in S. huberi and 27–61 μm in S. rosifolia. The mesocarp was also thicker in S. hedgeana. The wetted mericarps produced mucilage, but S. huberi differed from the others in having translucent-milky white opaque mucilage with fibres or radiating cordons.